Association between SNP and haplotypes in PPARGC1 and adiponectin genes and bone mineral density in Chinese nuclear families - Zhang Zhen-lin; He Jin-wei; Qin Yue-juan; Hu Yun-qiu; Li Miao; Liu Yu-juan; Zhang Hao; Hu Wei-wei (Acta Pharmacologica Sinica, 2016)
Aim: To assess the contribution of single nucleotide polymorphisms (SNP) and haplotypes in the peroxisome proliferator-activated receptor-γ co-activator-1 (PPARGC1) and adiponectin genes to normal bone mineral density (BMD) variation in healthy Chinese women and men. Methods: We performed populationbased (ANOVA) and family-based (quantitative trait locus transmission disequilibrium test) association studies of PPARGC1 and adiponectin genes. SNP in the 2 genes were genotyped. BMD was measured using dual-energy X-ray absorptiometry in the lumbar spine and hip in 401 nuclear families with a total of 1260 subjects, including 458 premenopausal women, 20–40 years of age; 401 postmenopausal women (mothers), 43–74 years of age; and 401 men (fathers), 49–76 years of age. Results: Significant within-family association was found between the Thr394Thr polymorphism in the PPGAGC1 gene and peak BMD in the femoral neck (P=0.026). Subsequent permutations were in agreement with this significant within-family association result (P=0.016), but Thr394Thr SNP only accounted for 0.7% of the variation in femoral neck peak BMD. However, no significant withinfamily association was detected between each SNP in the adiponectin gene and peak BMD. Although no significant association was found between BMD and SNP in the PPARGC1 and adiponectin genes in both men and postmenopausal women, haplotype 2 (T-T) in the adiponectin gene was associated with lumbar spine BMD in postmenopausal women (P=0.019). Conclusion: Our findings suggest that Thr394Thr SNP in the PPARGC1 gene was associated with peak BMD in the femoral neck in Chinese women. Confirmation of our results is needed in other populations and with more functional markers within and flanking the PPARGC1 or adiponectin genes region.